Temas culturales en el cuidado de enfermería (2002)
ABSTRACT: This paper is a revised version of a keynote lecture that was presented in several cultural competence conferences in the U.S and Sweden. The current version was presented as an open lecture at the University of Antioquia, Medellín, in August, 2000. It introduces the author's framework to guide culturally competent health care, which is a general approach that includes cultural knowledge, health provider self awareness, and the influence of the sociopolitical context. Cultural influences on health and illness perceptions and communication are described to inform, readers about potential varlations into which the may want to make inquiries. The remainder of the paper covers practical suggestions on how to improve cross-cultural communication, do a cultural assessment, and plan culturally appropriate interventions.